Multidrug resistant tuberculosis in Romania - Șoroagă, Maria Larisa (Calitatea Vieții, 2018)
Tuberculosis continues to be a public health concern in Romania. This article is focusing on resistant multidrug tuberculosis (TB-MDR) and the challenges of taking a long-term treatment. It begins with a brief history of tuberculosis, then the implications of the disease are discussed and it continues with presenting recent statistical data on new confirmed tuberculosis and multidrug resistant tuberculosis cases. In the second section is presented a qualitative research conducted using the face-to-face interview methodology. The aim of the research is to show, from the patient’s perspective, the implications of the disease from the moment of diagnosis with TB-MDR and until he/she returned to the community. These implications are also investigated from the perspective of the pneoumologist. A purposeful sample of ten patients was selected with different periods of hospitalization, both at the beginning and at the end of treatment, with different levels of education and different ages. Most of the respondents mentioned that they had support from the family, both emotionally and financially, but they also expressed the need for psychosocial support services during the hospital stay and after. The social implications of the disease mentioned by the respondents had negative consequences on the quality of their life, suggesting the need to increase the role of social services for people with TB-MDR.